Dr. Yellapragada Subba Rao: an Indo-American trailblazer in the field of medicine - Malla, Sreeharshita (International Journal of Research in Medical Sciences, 2025)
Dr. Yellapragada Subba Rao (1895-1948) was a pioneering biochemist whose contributions have left a profound impact on modern medicine. Born into a Telugu family in India, SubbaRao's educational journey took him from Madras Medical College to prestigious institutions like Harvard Medical School and the School of Tropical Medicine, London. Despite the interruption of his medical education due to his involvement in the Indian independence movement, SubbaRao made ground-breaking advancements in biochemistry. Notably, his collaboration with Cyrus Fiske led to the development of the Fiske-Subbarow Method for phosphorus estimation and elucidated the role of phosphocreatine and ATP in muscle function. His research on vitamin B12 significantly advanced the understanding of anaemia treatment, while his work on folic acid contributed to its synthesis and therapeutic applications. SubbaRao’s contributions extended to oncology and infectious diseases; his work was instrumental in developing methotrexate, an early chemotherapy drug and discovering chlortetracycline, the world’s first tetracycline antibiotic. His innovative biochemical assays and research on metabolic pathways have facilitated the development of various treatments and antibiotics, fundamentally shaping the field of drug discovery and clinical practice. Despite his passing at a young age, SubbaRao's legacy endures through his significant scientific achievements and the recognition of his contributions, including tributes such as a commemorative postal stamp and the naming of species and institutions in his honour. His work remains influential in on-going research and medical applications, underscoring his role as a key figure in the advancement of biochemistry and medicine.